Earliest western Atlantic staghorn corals (Acropora) from the lower Oligocene Suwannee Limestone of Florida, USA, and their significance for modern coral distribution. (November 2022) - Wallace, Carden C.; Portell, Roger W.
Abstract: The Suwannee Limestone of Florida and Georgia, USA, is a carbonate paleoenvironment with a rich diversity of marine fossils. These record the presence of coral- and seagrass-bearing communities in the western Atlantic from the Eocene/Oligocene boundary to the mid Oligocene (33.9–28.1 Ma). From the Suwannee Limestone, we describe two new species of the cosmopolitan, diverse, and abundant coral genus Acropora ("staghorn corals"), Acropora suwanneensis new species and Acropora upchurchi new species, which predate all other described Acropora species from the Americas and Caribbean by at least 10 million years. Diminutive skeletal structure in both species is indicative of their living in protected calm-water habitats. At their time of occurrence, an Atlantic–Pacific connection was open through Central America. Both species belong to morphological lineages also present in the fossil record of the eastern Atlantic (Europe, or the western Tethys). These lineages no longer occur in the Atlantic Ocean, but they are extant in the Indo-Pacific region, with the closest modern relative of each new species occurring in the Pacific Ocean to central Indo-Pacific. Some species in the two morphological lineages have existed for up to 20+ million years. The new species may have played a part in perpetuating a cosmopolitan Tethyan fauna and expanding Acropora habitats in the western Atlantic, by which they likely also contributed to the renowned species and habitat diversity of Acropora in the modern Indo-Pacific. UUID https://zoobank.org/40118623-8b82-4352-a065-b58da74a5c41